TECHNIQUES IN TEACHING ENGLISH SPEAKING SKILLS HIGH SCHOOL GENZ STUDENTS: CHALLENGES AND COPING STRATEGIES - Putri, Anggun Helmaya; Susiati, Susiati (Premise: Journal of English Education and Applied Linguistics, 2025)
Teaching English-speaking skills requires the right effort so that students can play an active role in the learning process. Therefore, this study aims to identify the techniques used by teachers in teaching English speaking skills, the challenges faced by teachers in teaching English Speaking Skills, and the coping strategies employed to address the difficulties encountered by teachers. This study uses a qualitative descriptive method to present data. The participants in this study were three teachers from a vocational high school in Sukoharjo who taught at different grade levels. Data were collected from observations of teaching and learning activities in the classroom and interviews with the three related teachers. After the data is collected, it will be analyzed by first simplifying the findings, grouping them, and concluding in the final stage. The results of the study showed that (1) Role-play, discussion, and presentation techniques are very effective in English language learning, (2) the challenges faced by teachers are students' lack of self-confidence, different student input, and differences in student interests, (3) the strategies used to deal with problems are forming small groups, level-based tasks, and linking speaking to interests. The results of this study aim to provide additional insights for teachers, thereby enhancing the effectiveness of the learning process.